British birds : a pocket guide - Hume, Rob; Still, Rob; Swash, Andy; Harrop, Hugh; Tipling, David (WildGuides., 2019)
"This innovative and carefully designed photographic guide provides a concise introduction to the identification of the 246 birds most likely to be seen in Great Britain and Ireland."